Agricultural Policy in the 21st Century: Economics and Politics. (March 2015) - Fulton, Murray
<x xml:space="preserve">Abstract</x> This paper provides a framework for thinking about agricultural policy, why and how it is introduced, and how it changes over time. This framework suggests that agricultural policy will be influenced by both concerns for efficiency and lobbying. While agricultural policy will not always be effective, it will be relatively stable, at least in terms of its broad outlines. Underlying this broad stability, however, will be considerable small‐scale change as program and policy details shift in response to a changing environment. When policy changes in a major way, which it almost always will, the shift will be abrupt—a punctuation. These abrupt changes come as attention is eventually paid to areas and/or issues that are increasingly understood to be not working. While there is considerable room for economic analysis in the policy process, it will not be the main driver; this role belongs to politics—the ability to change the discourse around a policy issue in such a way that different evaluations and interpretations of the policy and its impact are created. Based on the analysis in this paper, it is argued that supply management is more likely to see significant change than business risk management programs, since more attention seems to be currently directed at the former issue. It is also argued that although proponents of local food, organic production, and urban agriculture have had some success at getting attention focused on these issues, this success will not translate into any major policy changes, in part because markets for these products are developing and appear to be working reasonably well.